2017
DOI: 10.1007/s10565-017-9401-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced CCN1 production enhances interleukin-6 secretion in bronchial epithelial cells

Abstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a clinical complication caused by primary or secondary lung injury, as well as by systemic inflammation. Researches regarding molecular pathophysiology of ALI/ARDS are immerging with an ultimate aim towards developing prognostic molecular biomarkers and molecule-based therapy. However, the molecular mechanisms concerning ALI/ARDS are still not completely understood. The purpose of the present study was to identify a crucial role of CCN1 in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…53 Airway epithelial cells are involved in the secretion of several molecules as surfactant components and pro-inflammatory mediators. 54,55 Interleukin 6 (IL-6) and Interleukin 8 (IL-8) are strongly involved in respiratory acute lung injury. Pires-Neto et al showed that airway epithelial cells from patients with ARDS have increased expression of IL-8 and IL-6 compared with controls.…”
Section: Covid-19mentioning
confidence: 99%
“…53 Airway epithelial cells are involved in the secretion of several molecules as surfactant components and pro-inflammatory mediators. 54,55 Interleukin 6 (IL-6) and Interleukin 8 (IL-8) are strongly involved in respiratory acute lung injury. Pires-Neto et al showed that airway epithelial cells from patients with ARDS have increased expression of IL-8 and IL-6 compared with controls.…”
Section: Covid-19mentioning
confidence: 99%
“…The expression levels of inflammatory genes were measured in the presence of the Hh agonist (SAG) and antagonist (Cyclo). The responsiveness of DC2 cells to the inflammatory condition was first assessed by examining the expression level of interleukin‐6 (IL‐6), an LPS mediated‐inflammation factor 31,32 . After a 6‐hour treatment with LPS, IL‐6 expression was upregulated 2‐fold (Figure 5A), confirming DC2 responsiveness to the inflammatory condition.…”
Section: Resultsmentioning
confidence: 85%
“…A previous study has shown that A549 cells release IL-1β and TNF-α after LPS stimulation though autocrine modes (36). This exerts a strong and synergic induction signal for IL-6 (37), since a high increase of IL-6 in ALI/ARDS accelerates the development of the local inflammatory microenvironment (38). Moreover, high levels of IL-1β, IL-6 and TNF-α have been considered as the most promising biomarkers for predicting morbidity and mortality in patients with ALI/ARDS (39).…”
Section: Discussionmentioning
confidence: 97%